Telerehabilitation In Monitoring Treatment of Heart Disease Patients: Literature Review - Wahyuni Arni; Yuliana Syam; Syahrul Syahrul (STIKep PPNI Jawa Barat, 2022)
Aims: Heart disease is a chronic disease that affects the patient's physical and psychological adaptation. Currently, cardiac rehabilitation focuses on delivering rehabilitation components remotely using technology via telerehabilitation. Objective: The purpose of this review is to identify the use of telerehabilitation in monitoring signs and symptoms of heart disease. Methods: Literature review method with four databases PubMed, Proquest, Ebsco, Cochrane Library, Taylor & Francis database, and identification of gray literature, spanning 2011-2021, and 24 articles were reviewed. Results: The results of the review show that cardiac rehabilitation components are provided through various tele media mobile phones, messenger applications (SMS, QQ, and WeChat), videoconferencing, online information (websites, emails), e-visit, and virtual reality (VR). Telerehabilitation is useful in monitoring exercise capacity, resting systolic blood pressure, blood pressure control, ECG monitoring media, monitoring of dysrhythmias (atrial fibrillation/AF), complaints of fatigue, monitoring of dyspnoea symptoms, hemoglobin and electrolyte levels. sodium and potassium), and depressive symptoms. Conclusions: Telerehabilitation can be an alternative for continuous care of patients in monitoring signs and symptoms of heart disease, both physical and psychological aspects.